Relationship between knowledge, Unsafe Action and Management Factors with work accidents in palm oil processing works of PT. X Jambi - Dwi Jayanti (Universitas Widya Gama Mahakam Samarinda, 2024)
Background : The main Factors of accidents are caused by human factor and unsafe condition due to lack of discipline in the work environment, tools/machines, and poor environment. Objectives: This study aims to analize the relationship beetwen knowledge, unsafe action and management factors with work accidents in palm oil processing works of PT. X Jambi Research Metodes: The research design is cross sectional. The sample of this study is 100 workers. With the total sampling technique, data collection through interviews uses questionnaires.The independent variables are knowledge, Unsafe Action, supervision, training, and SOP implementation, while the dependent variables studied in this study are accidents that occur during work. Data analysis using chi-Square. Results: The proportion of workers who have experienced work accidents while working at PT. X by 51%. There was an association between knowledge (PR: 1,958; 95% 95% CI = 0.978-2,464; value=0.008), unsafe action (PR: 1,992; 95% CI = 1,201-3,302; p value=0.005), supervision (PR: 1,753; 95% CI = 1,753-2,643; p value=0.009. There was no association between Training (PR: 1,486; 95% CI = 1,005-2,198; p value=0.069) and SOP implementation (PR: 1,187; 95% CI = 0.810-1,738; p value=0.509) with work accidents. Conclusion: : Lack of knowledge, Unsafe Action and lack of supervision increase the risk of work accidents. Keywords: : Knowledge, Unsafe action, Supervision, training, SOP Implementation